Influence of food intrinsic factors on the inactivation efficacy of cold atmospheric plasma: Impact of osmotic stress, suboptimal pH and food structure. (December 2016) - Smet, C.; Noriega, E.; Rosier, F.; Walsh, J.L.; Valdramidis, V.P.; Van Impe, J.F.
Abstract: Cold atmospheric plasma (CAP) has proved to have great potential as a mild food decontamination technology. Different process parameters, including food intrinsic factors, are known to influence the resistance of the cells towards the treatment. The importance of osmotic stress (0, 2, 6% (w/v) NaCl) and suboptimal pH (5.5, 6.5, 7.4) on the CAP efficacy to inactivate Salmonella Typhimurium and Listeria monocytogenes is studied for various food structures. The helium-oxygen plasma was generated by a dielectric barrier discharge reactor, treating samples up to 10 min. If grown under osmotic stress or at suboptimal pH, microbial cells adapt and become more resistant during CAP treatment (stress hardening). Additionally, the microorganisms and the food structures also influence the inactivation results. This study illustrates the importance of increasing knowledge on food intrinsic factors, to be able to predict the final CAP inactivation result. Highlights: Intrinsic food factors influence the CAP inactivation efficacy. Osmotic stress and suboptimal pH growth conditions result in CAP resistant cells. The food structure impacts the CAP efficacy regardless of the environmental stress. The SI evolution in time suggests injury accumulation culminating in cell death.